Pemanfaatan Google Workspace For Education Bagi Guru Dalam Pembelajaran - Irani, Ni Kadek Chandra Putri (Metta : Jurnal Ilmu Multidisiplin, 2022)
This research has the aim of knowing as well as explaining the use of Google Workspace For Education for teachers in learning in the current Industry 4.0 era which affects the development of information and communication technology which is so significant in the Education section related to the implementation of teaching and learning. Teachers in today's digital age are required to increase their insight and professionalism in the field of information and communication technology-based in the learning process. This research uses a qualitative descriptive method and a research sample of 10 teachers at SD Negeri 1 Delod Peken Tabanan from various levels of education. The equipment needed for this research such as stationery, laptop, and also the Google Meet application in conducting interviews for search facilities. This research is expected to be able to provide insight into the needs of the current education era in terms of easy access to information and communication technology to assist teachers in improving the quality of education, one of which is Google Workspace For Education which provides various features that teachers can use in the learning process, namely Gmail. Meet, Classroom, Drive, Docs, Slides, Forms and Sheets.